THE GUILT OF BEING A WORKAHOLIC WOMAN IN LANDLINE BY RAINBOW ROWELL - IRMAWATI, IRMAWATI (LANTERN (Journal on English Language, Culture and Literature), 2017)
In this thesis, the writer analyzes a novel by Rainbow Rowell entitled Landline. The novel tells about a woman who is in confusion to choose between her family and her job. The purposes of the thesis are to analyze and to explain the guilt that is faced by the main character, Georgie McCool, and her attempt to resolve the guilt. Several theories such as the five stages of grief proposed by Elizabeth Kübler-Ross and the theory of guilt by Guy Winch are used in order to analyze the issue. Other theories regarding workaholism and stereotypes of woman from various experts are also used. In order to analyze the data, the writer uses internet and library research. After conducting the analysis, the result shows that the main character of the novel has more masculine than feminine traits. She also suffers from disloyalty guilt, and it forces her to undergo the five stages of grief, such as denial, anger, bargaining, depression, and acceptance.